2018
DOI: 10.1186/s12864-018-4615-z
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the phylogenetics and population structure of the prairie falcon (Falco mexicanus)

Abstract: BackgroundManagement requires a robust understanding of between- and within-species genetic variability, however such data are still lacking in many species. For example, although multiple population genetics studies of the peregrine falcon (Falco peregrinus) have been conducted, no similar studies have been done of the closely-related prairie falcon (F. mexicanus) and it is unclear how much genetic variation and population structure exists across the species’ range. Furthermore, the phylogenetic relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 110 publications
3
24
0
Order By: Relevance
“…Furthermore, Falco tinnunculus and Falco naumanni had a monophyletic relationship with 100% bootstrap value, while Falco columbarius and Falco sparverius were outgroups. This study further confirmed the monophyletic relationship existing among falcons ( Helbig et al, 1994 ; Wink et al, 2004 ; Nittinger et al, 2005 ; Doyle et al, 2018 ).…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, Falco tinnunculus and Falco naumanni had a monophyletic relationship with 100% bootstrap value, while Falco columbarius and Falco sparverius were outgroups. This study further confirmed the monophyletic relationship existing among falcons ( Helbig et al, 1994 ; Wink et al, 2004 ; Nittinger et al, 2005 ; Doyle et al, 2018 ).…”
Section: Discussionsupporting
confidence: 85%
“…The introduction of molecular markers promotes the taxonomy of fungi. Mitochondrial genomes have been widely used in phylogenetics, evolutionary and population genetics because of rapid evolution rates and many available molecular markers 75,76 . Mitochondrial cox1 gene and rRNA genes have been widely used in phylogenetic studies of animals 77,78 .…”
Section: Discussionmentioning
confidence: 99%
“…The phylogeny is adapted from Fuchs et al (2015). It is based on seven nuclear loci and one mitochondrial haplotype sequences, and two fossil calibration points corresponding to splits between subfamilies of Falconidae, and scaled by estimated divergence time At present, complete mitogenomes are available for nine species of falcons: the American kestrel (Gibb, Kardailsky, Kimball, Braun, & Penny, 2006), peregrine falcon (Ryu, Lee, & Hwang, 2012); merlin (Dou et al, 2016); saker falcon (Lu, Lu, Li, & Jiang, 2016); lesser kestrel ; gyrfalcon (Sveinsdóttir, Guðmundsdóttir, & Magnússon, 2017); prairie falcon (Doyle et al, 2018); amur falcon (Yang, Yang, Wang, Lu, & Li, 2018); and common kestrel (Unpublished, see NCBI Accession: EU196361). While these mitogenomes demonstrate similar patterns of organization to other raptors, they do contain a few intriguing features related to their control regions (Lu et al, 2016;Ryu et al, 2012;Sveinsdóttir et al, 2017;Yang et al, 2018).…”
Section: F I G U R Ementioning
confidence: 99%